Climate Services Can Support African Farmers' Context-Specific Adaptation Needs at Scale - Hansen, James; Vaughan, Catherine; Kagabo, Desire M.; Dinku, Tufa; Carr, Edward R.; Körner, Jana; Zougmoré, Robert B. (Frontiers Media, 2019)
We consider the question of what is needed for climate services to support sub-Saharan African farmers’ adaptation needs at the scale of the climate challenge. Consistent with an earlier assessment that mutually reinforcing supply-side and demand-side capacity constraints impede the development of effective climate services in Africa, our discussion of strategies for scaling up practices that meet farmers’ needs, and opportunities to address long-standing obstacles, is organized around: (a) meeting farmers’ climate information needs; (b) supporting access, understanding and use; and (c) co-production of services. A widespread gap between available information and farmers’ needs is associated with entrenched seasonal forecast convention and obstacles to using observational data. Scalable innovations for producing more locally relevant historical and forecast climate information for farm decision-making are beginning to be adopted. Structured participatory communication processes help farmers relate complex climate information to their experience, and integrate it into their management decisions. Promising efforts to deliver rural climate services strategically combine communication channels that include participatory processes embedded in existing agricultural advisory systems, and innovations in interactive broadcast media. Efforts to engage farmers in co-production of climate services improve delivery to farmers and dialogue among stakeholders, but often with little impact on the usability of available information. We discuss challenges and options for capturing farmers’ evolving demands, and aggregating and incorporating this information into iterative improvements to climate services at a national scale. We find evidence that key weaknesses in the supply and the demand sides of climate services continue to reinforce each other to impede progress towards meeting farmers’ needs at scale across Africa. Six recommendations target these weaknesses: (1) change the way seasonal forecasts are produced and presented regionally and nationally, (2) use merged gridded data as a foundation for national climate information products, (3) remove barriers to using historical data as a public good, (4) mobilize those who work on the demand side of climate services as an effective community of practice, (5) collectively assess and improve tools and processes for communicating climate information with rural communities, and (6) build iterative co-production processes into national climate service frameworks.